Examining the difference between 10- and 20-min of immersive virtual reality on symptoms, affect, and central sensitization in people with chronic back pain - Baker, Nancy A.; Polhemus, Augusta; Kenney, Megan; Bloch, Rina; Ward, Nathan; Intriligator, James; Edwards, Robert (Frontiers in Virtual Reality, 2023)
Immersive virtual reality (IVR) is increasingly used as a treatment for chronic pain. In this crossover randomized pilot study, we examined the effect of 10-and 20-minute dosages on back pain intensity, affect, and measures of pain sensitization in people with chronic back pain (CBP). Twenty-one people with CBP were seen for two visits of IVR. Participants were randomly assigned to receive either 10-or 20-minutes of IVR in Visit 1 and the other dosage in Visit 2. Our primary analyses were effect sizes and simple inferential comparisons for pain intensity, affect, fatigue, and measures of pain sensitization assessed using quantitative sensory testing. Overall, IVR had a moderate, significant effect in reducing back pain intensity, negative affect, and painful aftersensations. When dosage was examined, 20-minutes had a moderate, significant effect on pain while 10-minutes had a small, non-significant effect, although the between-dosage difference was non-significant. Interestingly, effects were much larger in Visit 1, particularly for 20-minutes, but this diminished in Visit 2, and both dosages had a smaller effect in Visit 2. We interpret these results to indicate that pain modulation may be associated with novelty and engagement that can attenuate over time if the IVR encounter is not sufficiently engaging. Moreover, that if participants are engaged in a single session, 20-minutes may be necessary to obtain sufficient competency with IVR, while in subsequent 2 This is a provisional file, not the final typeset article sessions, 10-minutes of IVR may be sufficient to affect pain. (https://clinicaltrials.gov/ NCT04307446)